Physical and chemical characteristics of gluten-free cookies based on the variation of mocaf flour and tofu dregs flour proportions: Karakteristik fisik dan kimia cookies gluten-free berdasarkan variasi proporsi tepung mocaf dan tepung ampas tahu - Prabowo, Ivy Dian Puspitasari; Tanone, Cindy Felicia (JITIPARI, 2025)
This study explores the effect of varying proportions of mocaf flour and tofu dregs flour on the physical and chemical characteristics of gluten-free cookies. The study was conducted using a Completely Randomized Design (CRD) with one factor: the proportion of mocaf flour and tofu dregs flour. The treatment levels were as follows: 45g mocaf flour + 15g tofu dregs flour, 30g mocaf flour + 30g tofu dregs flour, and 15g mocaf flour + 45g tofu dregs flour. Sensory evaluations (taste, aroma, appearance, and texture) and chemical analyses (moisture, protein, fat, and ash content) were conducted. The results indicate that the proportion of mocaf flour and tofu dregs flour significantly affects panelists' acceptance in terms of taste, aroma, and appearance. The most preferred formulation was 30g mocaf flour + 30g tofu dregs flour, with sensory scores of 3.80 for taste, 3.20 for aroma, 4.28 for texture, and 3.61 for appearance. Proximate analysis revealed that the product contained 2.58% moisture, 1.63% ash, 25.27% protein, and 24.86% fat.